(untitled) (Baghdad Science Journal, 2025)
This work aimed to design and testing of a computer program – based eyeQ improvement, photographic memory enhancement, and speed reading to match the reading speed 150 – 250 word per minute (WPM) with the mind ability of processing and eye snap shooting 5000WPM . The package designed based on Visual Basic 6. The efficiency of the designed program was tested on a 10 persons with different levels of education and ages and the results show an increase in their reading speed of approximately 25% in the first month of training with noticeable enhancement in the memory as well as an increase in the ability to read for longer time without feeling nerves or boring, a nonlinear continuously increase in reading speed is assured after the first month with a hope of reaching a target of 3000WPM within 3 – 5 years of training and that is what is called photographic memory where most of the read data processed in right side of the mind, the smaller age, and higher level of education is an effective factor on the results.